2008
DOI: 10.1182/blood-2007-04-085514
|View full text |Cite
|
Sign up to set email alerts
|

The role of Akt in the signaling pathway of the glycoprotein Ib-IX–induced platelet activation

Abstract: The platelet von Willebrand factor (vWF) receptor, glycoprotein Ib-IX (GPIb-IX), mediates platelet adhesion and induces signaling leading to integrin activation. Phosphoinositol 3-kinase (PI3K) is important in GPIb-IX–mediated signaling. PI3K–dependent signaling mechanisms, however, are unclear. We show that GPIb-IX–induced platelet aggregation and stable adhesion under flow were impaired in mouse platelets deficient in PI3K effectors, Akt1 and Akt2, and in human platelets treated with an Akt inhibitor, SH-6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
151
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(159 citation statements)
references
References 53 publications
7
151
1
Order By: Relevance
“…Although oral administration of hydroxyurea or ARQ 092 alone did not affect intracellular ROS generation in fMLP-stimulated neutrophils isolated from the mice, co-administration of hydroxyurea and ARQ 092 significantly decreased ROS generation, suggesting that combined therapy may efficiently attenuate oxidative stress conditions in SCD patients. Consistent with previous reports showing that the activation and adhesive function of platelets is regulated by AKT, [17][18][19]36 we found that ARQ 092 significantly impairs P-selectin exposure and GPIbα-mediated agglutination in platelets from SCD patients in vitro and in SCD mouse platelets ex vivo. In support of the importance of neutrophil αMb2 integrin and platelet P-selectin and GPIbα for neutrophil-platelet interactions, 13 we observed that specific AKT inhibition in both neutrophils and platelets isolated from SCD patients effectively decreases heterotypic cell-cell aggregation.…”
Section: Discussionsupporting
confidence: 81%
“…Although oral administration of hydroxyurea or ARQ 092 alone did not affect intracellular ROS generation in fMLP-stimulated neutrophils isolated from the mice, co-administration of hydroxyurea and ARQ 092 significantly decreased ROS generation, suggesting that combined therapy may efficiently attenuate oxidative stress conditions in SCD patients. Consistent with previous reports showing that the activation and adhesive function of platelets is regulated by AKT, [17][18][19]36 we found that ARQ 092 significantly impairs P-selectin exposure and GPIbα-mediated agglutination in platelets from SCD patients in vitro and in SCD mouse platelets ex vivo. In support of the importance of neutrophil αMb2 integrin and platelet P-selectin and GPIbα for neutrophil-platelet interactions, 13 we observed that specific AKT inhibition in both neutrophils and platelets isolated from SCD patients effectively decreases heterotypic cell-cell aggregation.…”
Section: Discussionsupporting
confidence: 81%
“…This should be further investigated in relation to future advancements in specific agonists and antagonists of each PKC isoform. Epinephrine-mediated α2A-adrenoceptor-coupled Gz signaling alone is known to be incapable of inducing full platelet aggregation, and activation of P2Y12 receptor-coupled Gi signaling, which leads to inhibition of adenylyl cyclase, is required (22)(23)(24). An elevated plasma level of NO has been observed in CA-HY compared to CA-GR (10), and NO is known to raise cAMP levels in platelets (25).…”
Section: Discussionmentioning
confidence: 99%
“…The role of SFK (Lyn) as well as the cGMP pathway in GPIb-IX signaling appears to be proximal to the receptor and is important in the stable platelet adhesion to von Willebrand factor under shear stress, independent of ADP secretion (17,32,33). It is recognized that SFK is important in the collagen-induced activation of the ITAM pathway because SFK mediates tyrosine phosphorylation of the ITAM motif of FcR␥ required for recruiting the downstream kinase Syk, which is required for collagen-induced platelet secretion and aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PI3K and Akt are known to promote platelet secretion and secretion-dependent platelet aggregation (16,20,53,54), and the effects of PI3K and Akt are mediated via the NO-sGC/cGMP-PKG pathway (20,32). In this study, we further show that 1) the SFK inhibitor, PP2, inhibited agonist-induced Akt phosphorylation, indicating that SFK is important in GPCR-mediated activation of the PI3K-Akt signaling pathway; 2) PP2 and Lyn knock-out also inhibited thrombin-and collagen-induced increases in the intracellular cGMP levels in platelets, indicating that SFK is upstream of the NO-cGMP signaling pathway; 3) supplementation of low concentrations of 8-bromo-cGMP corrected the platelet aggregation defect caused by PP2 and Lyn knock-out and partially but significantly reversed the inhibitory effect of PP2 on platelet granule secretion, indicating that SFK (Lyn)-mediated activation of the cGMP signaling pathway plays an important role in the stimulatory effect of SFK (Lyn) on platelet secretion and aggregation; and 4) similar to PP2, the specific sGC inhibitor ODQ inhibited platelet aggregation in response to low dose thrombin (19).…”
Section: Discussionmentioning
confidence: 99%